2016
DOI: 10.1016/j.nicl.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating among degenerative parkinsonisms using advanced 123 I-ioflupane SPECT analyses

Abstract: 123I-ioflupane single photon emission computed tomography (SPECT) is a sensitive and well established imaging tool in Parkinson's disease (PD) and atypical parkinsonian syndromes (APS), yet a discrimination between PD and APS has been considered inconsistent at least based on visual inspection or simple region of interest analyses. We here reappraise this issue by applying advanced image analysis techniques to separate PD from the various APS.This study included 392 consecutive patients with degenerative parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Several previous studies have demonstrated lower overall striatal DAT binding in PSP and MSA-P than PD, with relative sparing of the caudate nucleus in PD (4,8,9,14). Already in early disease stages, patients initially diagnosed with PD that later converted to MSA or PSP have lower DAT binding in the caudate nucleus than patients in whom a diagnosis of PD is maintained (4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several previous studies have demonstrated lower overall striatal DAT binding in PSP and MSA-P than PD, with relative sparing of the caudate nucleus in PD (4,8,9,14). Already in early disease stages, patients initially diagnosed with PD that later converted to MSA or PSP have lower DAT binding in the caudate nucleus than patients in whom a diagnosis of PD is maintained (4).…”
Section: Discussionmentioning
confidence: 98%
“…Literature on the role of extrastriatal SERT in the differential diagnosis of PD, MSA, and PSP is scarce. Nevertheless, higher SERT binding has been observed in the midbrain and pons of PD patients relative to MSA-P and PSP patients (10,20), and whole brain analysis has been reported to be informative before (14). In the hypothalamus, SERT has been shown to be ubiquitously present in controls in a postmortem human brain study (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other supportive evidence to support a diagnosis of PD 6 . UK PDS criterion is met, when bradykinesia is associated with one of the symptoms of rigidity, 4-6 Hz resting tremor or postural instability 17 .…”
Section: Rating Scalesmentioning
confidence: 99%
“…APS has rapid and poor prognosis and in most cases, a duration of less than 10 years results in death 16 . Poor prognosis is typically due to the, fact that there has been less success with pharmacologic treatment and therapeutic options for APS is limited compared to PD 17 .…”
Section: Introductionmentioning
confidence: 99%